Provision of low cost media options for in vitro culture of Celosia sp. - Daud, Norhayati; Taha, Rosna Mat; Noor, Nor Nafizah Mohd; Alimon, Hasimah (Academic Journals, 2011)
The composition of culture medium used for shoot regeneration has a great influence on cost of materials making of media. This study was conducted to investigate the effect of using four kinds of commercial starch or flour as alternative gelling agents and coconut water as an organic additive in the culture medium on the number of shoots produced for eight weeks in culture. Explants from stem segments of Celosia sp were cultured on medium containing either half strength of Murashige and Skoog (MS) or without MS combined with 100 g/l of each gelling agents and 70 ml/l coconut water. The findings showed that the use of young coconut water and alternative gelling agents have response to in vitro shoots regeneration of stem segments of Celosia sp. Higher revenue (12.33 +/- 7.27) of shoots derived from stem segments results from the cultured media containing 100 g/l of potato starch, 70 ml/l coconut water, household sugar and half strength concentration of MS (1/2 MS). Statistical analysis found no significant difference (P>0.05) between culture media with different concentrations of MS with the number of shoots produced. The substitution of alternative gelling agents, use of coconut water and quantities of MS powder can reduce costs to medium preparation.